An Underappreciated Radiation Hazard from High Voltage Electrodes in Vacuum. Issue 1 (January 2017) - West, Adam D.; Lasner, Zack; DeMille, David; West, Elizabeth P.; Panda, Cristian D.; Doyle, John M.; Gabrielse, Gerald; Kryskow, Adam; Mitchell, Corinne
Abstract : Abstract: The use of high voltage (HV) electrodes in vacuum is commonplace in physics laboratories. In such systems, it has long been known that electron emission from an HV cathode can lead to bremsstrahlung x rays; indeed, this is the basic principle behind the operation of standard x-ray sources. However, in laboratory setups where x-ray production is not the goal and no electron source is deliberately introduced, field-emitted electrons accelerated by HV can produce x rays as an unintended hazardous byproduct. Both the level of hazard and the safe operating regimes for HV vacuum electrode systems are not widely appreciated, at least in university laboratories. A reinforced awareness of the radiation hazards associated with vacuum HV setups would be beneficial. The authors present a case study of a HV vacuum electrode device operated in a university atomic physics laboratory. They describe the characterization of the observed x-ray radiation, its relation to the observed leakage current in the device, the steps taken to contain and mitigate the radiation hazard, and suggested safety guidelines.